Optimization of Tourism Management, Promotion of Tourist Attractions, and Creative Economy Based on Android Application in Kulu Village, Wori District, North Minahasa Regency - Mita Takaendengan; Vincentius Pantow; Maruto Loegimin; Kevin Pangemanan (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Kulu Village is one of the villages in North Minahasa Regency with untapped tourism potential. The research object is Kulu Village, North Minahasa Regency, which has the potential for diving spots, fishing spots, mangrove forest, paniki Island, legend of posi-posi kuning, local culture and traditions that have not been optimized, as well as the Kulu village community, which has creative economic businesses. Therefore, this research aims to optimize the tourism management model, promote tourist attractions, and develop creative economies based on Android (Website & All Social Media Platforms) in Kulu village. The research method used is the Qualitative Method with data collection techniques of observation, interviews, and questionnaires. Information is obtained from stakeholders, including the village government, tourism economic actors, and the community related to tourism, the promotion of tourist attractions, and the creative economy in Kulu village. Meanwhile, the data analysis technique uses the Scoring system and FGD (Focus Group Discussion). The research concluded that Kulu Village's tourism potential can be maximized through infrastructure improvements, digital promotion via websites and social media, local product integration, and stakeholder partnerships. Developing an Android-based web application and providing community training is crucial for promoting tourism and enhancing the local creative economy. Kulu Village has rich natural and cultural tourism potential. However, to fully harness this potential, infrastructure improvements, institutional strengthening, and promotion through websites and social media platforms like Instagram, Facebook, TikTok, and YouTube are essential to attract both local and international tourists. Strengthening partnerships with stakeholders, such as travel agents, online booking platforms, and influencers, is also crucial to increase the visibility of Kulu Village's tourism destinations. Additionally, local products such as handicrafts and traditional cuisine can be integrated into the tourism ecosystem through digital platforms, including websites and social media